2015
DOI: 10.18488/journal.23/2015.4.3/23.3.111.120
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Assisted Language Learning (Call): Pedagogical Pros and Cons

Abstract: Computer-Assisted Language Learning (CALL) has begun a revolution in the domain of language pedagogy. Before the presence of technology, learning a language with the old-fashioned methods could not meet the learners' needs and what they expected from language for an effective communication. In addition, in the absence of software programming and so many other facilities by which learners could enhance their language abilities quickly, learning came to be tediously time-consuming. Therefore, the purpose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…In relation to those mentioned problems, some relevant studies also found several similar problems in CALL implementation, namely networking, computer facilities, and learner autonomy since not all students had a computer and good internet connection and not all of them could be autonomous learners (Derakhshan et al, 2015;Diana & Ciornei, 2013). These findings were in line with the current research even though the current research found new problems.…”
Section: Pre-service English Teachers' Hindrances During Call Implemesupporting
confidence: 88%
See 1 more Smart Citation
“…In relation to those mentioned problems, some relevant studies also found several similar problems in CALL implementation, namely networking, computer facilities, and learner autonomy since not all students had a computer and good internet connection and not all of them could be autonomous learners (Derakhshan et al, 2015;Diana & Ciornei, 2013). These findings were in line with the current research even though the current research found new problems.…”
Section: Pre-service English Teachers' Hindrances During Call Implemesupporting
confidence: 88%
“…Furthermore, some researchers did conceptual papers on CALL. These conceptual papers contain the theory of CALL, such as CALL as teaching and learning media (Rachmawati, 2016), challenging issues of CALL (Garrett, 2009;Tal & Yelenevskaya, 2012), pros and cons of CALL (Derakhshan et al, 2015;Diana & Ciornei, 2013), history, merits, and barriers of CALL (Primani & Agustrianti, 2017;Tafazoli & Golshan, 2014) and CALL in the curriculum of foreign language learning (Soleimani & Alaee, 2014). These conceptual papers were distinct from the current research because the current research is not a conceptual paper.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important concept as it plays a crucial role in language learning and teaching. This statement was supported by Derakhshan, Salehi, and Rahimzadeh (2015) stating that the students' successes and failures in learning the novel was heavily influenced by how much they enjoyed the novel and the efforts given by the students towards learning and appreciating the novel. Through the study, we noted that students with a more positive attitude spent more time and effort to learn and read the chapters of the novel, understand the underlying messages and values and important events that occurred in the novel.…”
Section: Purpose and Motivationmentioning
confidence: 94%
“…The incorporation of the above features in a rich digital learning platform captures learners’ attention and provides contextualized cues which eases learners’ comprehension difficulties and enhances their motivation in communication and language learning (Butler, Someya, & Fukuhara, 2014 ; Derakhshan, Salehi, & Rahimzadeh, 2015 ; Lin, Chen, & Liu, 2017 ). More importantly, the presence of up-to-date sound and visual effects in electronic devices can reflect real-life situations, which enables more exciting discussions among learners.…”
Section: Multimodality In Communicationmentioning
confidence: 99%